Exploring the relationship between teacher job satisfaction and professional development in urban schools during a pandemic - Juhji Juhji; Encep Syarifudin; Supardi Supardi; Paiman Paiman; Dina Indriana; Sutanto Sutanto; Irma Yunita Ruhiawati; Ima Rahmawati (Institute of Advanced Engineering and Science, 2023)
Job satisfaction and professional development are the talks of teachers in facing the challenges of 21st-century learning, where they must be able to adapt to the progress and development of information and communication in technology. Therefore, this article aims to analyze teacher job satisfaction, professional development, and the interaction between the two during the pandemic. A total of 232 public and private school teachers in urban areas were used as research samples. The sampling technique used a random technique. The research used an instrument developed and validated, then distributed through the principal and school supervisor, and the data were analyzed using the correlation technique. During the pandemic, the results revealed a high level of job satisfaction for state Islamic school teachers and a low level of job satisfaction for private Islamic school teachers, as well as a high level of professional development in both public and private Islamic schools and a moderate positive correlation between teacher job satisfaction and professional development in urban schools. Therefore, teachers should develop and carry out professional development in facing the challenges of 21st-century learning.